DOI: 10.31274/rtd-180813-5343
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of selected secondary students toward family planning education

Abstract: The generalizations drawn from this study are limited to the sample of selected Iowa high school students studied. Participants were selected from students of teachers who attended a workshop on parent education at Iowa State University in December, 1978. Assumptions It was assumed that the researcher would be able to develop an instrument to measure attitudes toward family planning education which would be interpreted consistently by the respondents, and that the respondents would be willing to respond to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Out of that number, approximately 60% of STDs and infections occur in people younger than 25 years. Past experience with young people shows that they get knowledge about sexuality mostly from unreliable sources, such as television, magazines and “experience exchange” with peers and older adolescents (4). Information about “delicate topics” at home is scarce and insufficient, as well as school curricula (5).…”
Section: Introductionmentioning
confidence: 99%
“…Out of that number, approximately 60% of STDs and infections occur in people younger than 25 years. Past experience with young people shows that they get knowledge about sexuality mostly from unreliable sources, such as television, magazines and “experience exchange” with peers and older adolescents (4). Information about “delicate topics” at home is scarce and insufficient, as well as school curricula (5).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study of teens examined the variables of age, sex, religion, occupation of mother, and occupation of father to find possible relationships of their attitudes toward sex education in the schools (Mercier & Hughes, 1981). Sex differences, according to this study, have a major effect on the respondents' attitudes toward family planning education.…”
Section: It Is Noteworthy That the Unitedmentioning
confidence: 81%
“…Although it is not the only factor having an effect, males and females have been socialized in different ways regarding sexuality and attitudes toward sexual activity (Mercier & Hughes, 1981). Darling and Hicks (1982), in a study of parental messages to adolescents about sexuality, found that parents transmit quite different messages to their daughters and their sons.…”
Section: It Is Noteworthy That the Unitedmentioning
confidence: 99%
See 2 more Smart Citations